2023
DOI: 10.1590/0103-8478cr20220071
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis and near-infrared spectroscopy in canola crop

Abstract: This study measured the effect of the association between agronomic traits related to the yield of canola grains grown at different sowing dates through path analysis. Another objective was to obtain a method to predict the oil content in the grains, fitting a multivariate model through near-infrared (NIR) spectroscopy analysis. The experiment was conducted in the field using a randomized block design in plots subdivided by time, with four plots (sowing dates), six subplots (canola hybrids), and four replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…This is a result of a smaller number of siliques per plant, combined with unfavorable weather conditions for flowering and development of the siliques (Figure 2 and Table 5). Other studies conducted in other regions of the country show that delays in sowing cause a reduction in grain yield (Rosa et al, 2020;Araújo et al, 2021;Santiago et al, 2022), as observed in this study.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This is a result of a smaller number of siliques per plant, combined with unfavorable weather conditions for flowering and development of the siliques (Figure 2 and Table 5). Other studies conducted in other regions of the country show that delays in sowing cause a reduction in grain yield (Rosa et al, 2020;Araújo et al, 2021;Santiago et al, 2022), as observed in this study.…”
Section: Resultssupporting
confidence: 87%
“…Different researchers report that different canola hybrids respond to sowing dates, and in general, cultivation carried out between the first fortnight of February and the first fortnight of March in the Center-South region of Brazil obtained the best responses in crop yield (Rosa et al, 2020;Araújo et al, 2021;Santiago et al, 2022). In the Agricultural Zoning of Climate Risk (MAPA, 2021) for canola, it is reported that the months of February and March are the best growing seasons, depending on the cycle of the hybrid to be used.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported its potential in warmer climates, particularly for grain production in the Brazilian Cerrado, given its protein and oil content of approximately 24 to 27 and 38%, respectively (Rigon et al, 2017). However, research aimed at developing crop management technologies remains scarce, with a need for investment in breeding programs to ensure significant yield gains and, consequently, expansion of the planted area (Santiago et al, 2022).…”
Section: Introductionmentioning
confidence: 99%